The wage impact of undocumented workers - Julie L. Hotchkiss; Myriam Quispe-Agnoli; Fernando Rios-Avila (Federal Reserve Bank of Atlanta, 2012)
Using administrative, individual-level, longitudinal data from the state of Georgia, this paper finds that a documented worker employed by a firm that hires undocumented workers can expect to earn 0.15 percent less than if employed by a firm that does not hire undocumented workers. However, in sectors where there are opportunities for task specialization and benefits from communication skills, documented workers can expect to earn a wage premium of less than 1 percent from being employed at a firm that also hires undocumented workers.
Keywords: J30; J15; 330; illegal immigrants; immigration; unauthorized immigration